Characteristics and Challenges of Cuban Freemasons in the twentieth century. A demographic approach - Romeu, Jorge Luis (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2013)
We present a statistical and historical analysis of the development of the Grand Lodge of Cuba during 1945–2010, based on our demographic study of this institution. Research identifies and evaluates important factors that have contributed to membership growth and decline, in the second half of the 20th Century. Important characteristics of this institution are identified and discussed, as they relate to the development of the evolving Cuban civil society.